Creativity Based Tourism in Kampung Kreatif Dago Pojok Bandung - Kresna Agung Wisesa; I Made Adhi Gunadi; Yustisia P. Mbulu (Fakultas Pariwisata Universitas Pancasila, 2018)
In this current era, many villages in Indonesia carry the concept of Tourism Village. One of them is a creative village located in Dago Pojok Bandung, West Java. This study aims to find out about tourism products and identify how the application of creativity based tourism in the Dago Pojok creative village. Data collection is done by descriptive qualitative method with observation and interview techniques. The variables used are the concept of tourism products consisting of tourist attractions and activities, accommodation facilities and services, other facilities and services (supporting facilities), transportation facilities and services, infrastructure and other institutions, and the concept of creativity based tourism consisting of local artists, ideas/knowledge and interaction. Based on the results and discussion, it can be concluded that tourism products in Dago Pojok creative village are tourism products based on culture, creativity, and art. Dago Pojok creative village is a tourism that is based on creativity, because the elements of Local Artisan, Idea or Knowledge, and Interaction have fulfilled the requirements in implementing tourism with the concept of creativity, but there are some thingsthat need to be improved, namely in the part of interaction it hasn't been carried out optimally.